PERAN UNIT REHABILITASI SOSIAL KARYA MANDIRI KABUPATEN PEMALANG DALAM PEMERATAAN PENDIDIKAN BAGI ANAK PUTUS SEKOLAH - Firmansyah, Yogie (Solidarity: Journal of Education, Society and Culture, 2013)
Poverty is a major factor inhibiting the advance of education in poor communities in the district. Most residents in the district of Pemalang livelihood as farmers. Economic level of society in Pemalang can be seen from the yields obtained, poverty in the communities in the district of Pemalang it also resulted in her childrens education level. Pemalang district is one of the districts with the number of children who are high school dropouts. The number of school dropouts in the district of Pemalang generally caused due to cost constraints experienced by poor families, and is unable to provide adequate access to education or the equivalent of their children. These problems are invited concern from Social Services in the District Immigration Office, through the Social Rehabilitation Unit works under the auspices of the Independent Center of Social Rehabilitation Distrarastra Pemalang II, which is one form of government concern for the presence of children dropping out of school. Independent Social Work Rehabilitation Unit providing free education for school dropouts who generally come from poor families and aims to reduce the number of children dropping out of school in the district of Pemalang